2002
DOI: 10.1089/153110702753621349
|View full text |Cite
|
Sign up to set email alerts
|

Planetary Resources and Astroecology. Planetary Microcosm Models of Asteroid and Meteorite Interiors: Electrolyte Solutions and Microbial Growth— Implications for Space Populations and Panspermia

Abstract: Planetary microcosms were constructed using extracts from meteorites that simulate solutions in the pores of carbonaceous chondrites. The microcosms were found to support the growth of complex algal and microbial populations. Such astroecology experiments demonstrate how a diverse ecosystem could exist in fluids within asteroids, and in meteorites that land on aqueous planets. The microcosm solutions were obtained by extracting nutrient electrolytes under natural conditions from powders of the Allende (CV3) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 36 publications
5
20
0
Order By: Relevance
“…4) [8,9,14]. We also found that brine shrimp eggs can uptake meteorite materials and can hatch in meteorite extracts, which shows that the extracts are not significantly toxic.…”
Section: Biomass Yield From Element (G/kg)mentioning
confidence: 51%
See 3 more Smart Citations
“…4) [8,9,14]. We also found that brine shrimp eggs can uptake meteorite materials and can hatch in meteorite extracts, which shows that the extracts are not significantly toxic.…”
Section: Biomass Yield From Element (G/kg)mentioning
confidence: 51%
“…The biomass that can be constructed from element x in a resource material is given by Equation (3) [8,9].…”
Section: Relations Between Resources and Biomassmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggestion has been criticised (Gualtieri, 1977). Planetary microcosms models of asteroids and meteorites also suggest that protoplanetary nebulae might support and disperse micro-organisms (Mautner, 2002). Wickramasinghe (2004) has been one of the great supporters of the panspermia theory and has gathered considerable evidence in its favour (Wallis et al, 1992;Sommer and Wickramasinghe, 2005).…”
mentioning
confidence: 99%